Automated configuration of organic Rankine cycle system based on process simulations. (1st February 2022) - Tang, Jianping; Kang, Lixia; Liu, Yongzhong
Highlights: An automated scheme for the optimal configuration of organic Rankine cycle (ORC) system is proposed. For ORC systems with the most common working fluids and heat sources are comprehensively simulated. The influences of the ORC structure and working fluid on thermodynamic performance are explored. The "double Pinch" rule for single-pressure and double-pressure evaporation ORC systems is verified. A linear relationship is established to determine multi-stage evaporation potential of a working fluid. Abstract: In organic Rankine cycle (ORC) system, the selection of the structure and the optimization of operating parameters are usually studied separately, which makes the existing design principles inadequate to describe the impacts of the structure on ORC performance, and thus greatly limits its practical applications. To this end, this paper addresses an automated scheme for the optimal configuration of the ORC system, aiming to simultaneously determine the working fluid, the structure and the operating parameters corresponding to the maximal system efficiency. In this work, a comprehensive simulation and optimization of four common ORC structures is first conducted with 18 working fluid candidates and the most common heat sources with the inlet temperature ranging at 200–120 °C. The influence mechanisms of the ORC structure on the thermodynamic performance of the ORC system are then explored to generalize the qualitative and quantitative principles for ORC configuration. Results show that, for the single-pressure evaporation ORC (SPC) with a given inlet temperature of the heat source, the Pinch point type formed by the working fluid and the heat source changes from vaporization Pinch point (VPP) to VPP&PPP (preheat Pinch point) and then to PPP as the critical temperature of the working fluid decreases. The system efficiency of SPC reaches its maximum when the double Pinch point of VPP and PPP is formed and double-pressure evaporation ORC (DPC) reaches its maximum system efficiency when the double Pinch points of HVPP and LVPP are formed. Besides, it is found that when compared with the basic ORC, the regenerative ORC enables to improve the thermal efficiency and system efficiency of the system at the same time, whereas the bleeding regenerative ORC increases the thermal efficiency while reduces the system efficiency. For the DPC, the type of Pinch point formed by the heat source and the working fluid in the optimal working condition is the key to determine whether a system has multiple evaporation potential. Specially, for the heat source with variable inlet temperature, a linear relationship between the inlet temperature of the heat source and the critical temperature of the working fluid can be established to determine the multiple evaporation potential of a certain working fluid. Based on these results, an automatic scheme for ORC configuration is developed and expected to provide an effective guidance for the selection of working fluid, configuration optimization and parameter determination of the actual ORC heat recovery process.